Effect of sodium dodecyl sulphate on the rheological and carbon sequestration properties of cemented paste backfill with CO2 injection - Shen, Zhuo; Zhou, Yibo (Frontiers in Earth Science, 2024)
Cemented paste backfill (CPB) is a technology that has a positive impact on both the environment and mining safety. In recent years, it has been widely applied and developed. To improve the carbon sequestration efficiency of CPB, air-entraining agent addition to CO2-injected CPB (CO2-CPB) has been proposed. However, the influence of air-entraining agents on the rheological and carbon sequestration properties of CO2-CPB has not been investigated to date. Therefore, sodium dodecyl sulphate (SDS), an air-entraining agent, was selected in this study, and the rheological and carbon sequestration properties of CO2-CPB added with SDS were comprehensively investigated. CO2-CPB samples with 0.0‰, 0.5‰, 1.0‰, and 1.5‰ SDS were prepared, and the rheological parameters (yield stress and viscosity) were tested after curing for 0, 0.25, 1, and 2 h. Gas content testing, microscopic analysis, and zeta potential measurements were performed. The results show that SDS addition decreased the yield stress and viscosity of CO2-CPB at 0–1 h; however, the yield stress and viscosity increased at 2 h. SDS addition significantly improved the carbon sequestration performance of CO2-CPB. The findings of this study have important implications for carbon sequestration development in CPB and solid waste utilisation.